Deteksi Birahi Guna Peningkatan Produktivitas Ternak Sapi di Kabupaten Pamekasan - Widyananda, Cepryana S; Shamad, Zulfaini; Purdiyanto, Joko; Agustina, Desi Kurniati; Susanti, Rina; Nafilah, Septi Sautin; Nurdiana, Alfin (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Signs of lambing in livestock are very diverse and will differ from one livestock to another. In fact, farmers assume that livestock that often make sounds are livestock that are in the phase of lambing, even though there are many factors that cause livestock to make sounds, such as hunger, unhealthy body conditions and feeling threatened. The purpose of this service is to provide solutions to partner problems, namely by conducting socialization of detection of lambing to increase farmers' knowledge of the timeliness of mating their livestock. The method of implementing the activity is divided into three stages, namely preparation, implementation and evaluation of the implementation of activities. The socialization activity was attended by 40 cattle farmers in Panaguan Village, the material presented included the heat cycle, signs of heat and the right mating time. At the end of the activity, a direct evaluation was also carried out using interview techniques, the socialization participants stated that they had gained new knowledge and were satisfied with the activities that had been carried out. This socialization activity was able to provide more understanding to farmers regarding the importance of conducting proper and accurate detection of lambing. Farmers as the audience gained new knowledge about the physical and behavioral signs of lambing in cattle.